PERBANDINGAN PEMILIHAN PRESIDEN DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA DENGAN KONSEP SYURA DALAM PRINSIP KETATANEGARAAN ISLAM - Muhammad Ihsan; Hasballah Thaib; Faisal Akbar Nasution; Edy Ikhsan (Universitas Sumatera Utara, 2016)
ABSTRACTPresidential election process in Indonesia has been reflected in the Constitution of the Republic of Indonesia Year 1945 (1945 Constitution). Since 1945, the presidential election process in Indonesia is consensus in an institution of the People's Consultative Assembly (MPR). It is as the implementation of the Preamble of the 1945 Constitution, all four precepts of Pancasila,